Pengaruh Kebijakan Deviden, Hutang, Profitabilitas, Pertumbuhan Perusahaan dan Kepemilikan Manajerial Terhadap Nilai Perusahaan pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Khrystie Haryuning Marthen; Titiek Suwarti (J-MAS (Jurnal Manajemen dan Sains), 2023)
Firm value was a goal that must be achieved in the context of the welfare of shareholders. This study aims to examine the effect of dividend policy, debt policy, profitability, company growth and managerial ownership on company value in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021.The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. Sampling by purposive sampling with a total sample of 150 companies. The data analysis technique used in this study uses multiple regression analysis.Based on the results of the research conducted, it shows that dividend policy has a negative and insignificant effect on firm value, debt policy has a negative and insignificant effect on firm value, profitability has a positive and significant effect on firm value, company growth has a negative and significant effect on firm value, managerial ownership positive and significant effect on firm value